Affirmative action: Meaning, intentions, and impacts in the big picture - Satu Kuitunen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper provides a broad overview of the meaning of affirmative action and its intended and unintended impacts. The paper is a literature review and does not make any arguments specifically for or against affirmative action but describes the broad arguments and findings in the existing literature. Central to the definition of affirmative action is its proactive nature in rectifying horizontal inequalities and historical wrongdoing. Motivations can be ethical, economic, or political. The designation criteria and the scope of affirmative action also vary across countries, which affects how its effectiveness and value are measured. Affirmative action can have positive intended impacts as well as adverse unintended impacts, and the jury is still out on its overall effectiveness. Affirmative action has also been implemented on the grounds of conflict management, but the results have been mixed, and the evidence of affirmative action as a conflict management tool is limited.
Keywords: I38; J15; 330; affirmative action; horizontal inequalities; literature review